Perfil das exposições ocupacionais a material biológico entre profissionais de saúde do Hospital de Base de Bauru: Medidas preventivas e pós-exposição - De Lima, Geovana Momo Nogueira; Kawanami, Gustavo Hideki; Romeiro, Fernando Gomes [UNESP] (EDITORA SCIENTIFIC, 2017)
Background: Exposure to biological materials is common among hospital workers, even when preventive measures are suggested. Few studies assessed the incidence of this type of exposure and the impact of preventive measures. Objective: The aim of the present study was to describe occupational exposure to biological materials at Base Hospital of Bauru, São Paulo, Brazil, along one year. Methods: Observational retrospective study conducted with data for 2014, which were analyzed according to epidemiological and occupational exposure characteristics before and after exposure, such as previous immunization and follow up of workers, respectively. Results: Forty-two accidents involving biological materials were recorded; 85.7% affected the nursing staff, mainly nursing technicians. The incidence of accidents involving sharp materials was 83%; the upper limbs were the most frequently affected (81%) body part. Vaccination campaigns and specific care protocols achieved effective results, allowing to avoid disease transmission and reducing the costs associated with the follow up of affected healthcare professionals. Few accidents (17%) occurred during emergency procedures, which shows that most instances of exposure might be prevented through safety measures. Conclusion: The study revealed some aspects of the workers involved, exposure type and follow up after accidents with biological materials at the investigated hospital and discusses measures likely to reduce risk.
Occupational exposures to biological material among health professionals of Bauru Base Hospital: Preventive and post-exposure measures
Keywords: Accident prevention; Environmental exposure; Occupational risks